Why do children worry about their academic achievement? An expectancy-value perspective on elementary students' worries about their mathematics and reading performance - Lauermann, Fani; Eccles, Jacquelynne S.; Pekrun, Reinhard (ZDM, 2017)
Children's worrying about their academic performance has profound implications for their learning and wellbeing in school. Understanding the contextual and psychological antecedents of students' worry thus represents an important area of research. Drawing on Eccles and colleagues' expectancy-value theory and Pekrun's control-value theory and using data from the Childhood and Beyond Study, we examined the motivational underpinnings of elementary students' worries about performing poorly in the domains of mathematics and reading (N = 805, grades 3, 4 and 6). With one exception, the analyses confirmed that children's expectations of success in and valuing of mathematics and reading interacted in predicting children's worry about these domains. Children's worry was strongest when they rated their subjective abilities and expected success in mathematics and reading as relatively low but perceived these subjects as valuable. Moderated mediation analyses further suggested that when children's self-concepts of mathematics and reading ability were low to moderate, students' perceived parental valuing of their performance in these subjects indirectly positively predicted children's worry via its positive impact on children's own subjective valuing of mathematics and reading. Thus, when children perceive high academic performance as potentially difficult to attain, perceived parental valuing might negatively impact their wellbeing in school (by increasing not only their valuing of mathematics and reading, but also their performance-related worrying). Children's gender, grade level, teacher-rated mathematics and reading aptitude, and prior self-reported worry about mathematics and reading performance were included as control variables in all analyses. [Author abstract]